2000
DOI: 10.1103/physrevb.61.12
|View full text |Cite
|
Sign up to set email alerts
|

Directional effects of heavy-ion irradiation in Tb/Fe multilayers

Abstract: Deposition of a 57 Fe probe layer at the top of iron layers in Tb/Fe multilayers has allowed us to study locally the atomic mixing induced by high-energy heavy-ion irradiation at the Tb-on-Fe interface. The structural and magnetic transformations induced by ion irradiation of the probe layer were investigated by 57 Fe conversion electron Mössbauer spectrometry. To study directional effects of the ion beam, we have irradiated a stack of two pieces of the same multilayer set face to face. No change in the averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Recently, in an interesting experiment, Juraszek et al have studied a possible directional effect of swift heavy ion irradiation in Tb/ Fe multilayers by irradiating two identical multilayers kept face to face with each other, thus making the Pb ions traverse the two multilayers in opposite directions ͑i.e., Tb to Fe and Fe to Tb͒. 29 Sensitivity to Fe-on-Tb interface was achieved by depositing a 0.5 nm thick 57 Fe marker layer at the interface, and using conversion electron Mössbauer spectroscopy to detect the changes at the interface. It was concluded that intermixing at the Fe/ Tb interface is not affected by the direction in which 11.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in an interesting experiment, Juraszek et al have studied a possible directional effect of swift heavy ion irradiation in Tb/ Fe multilayers by irradiating two identical multilayers kept face to face with each other, thus making the Pb ions traverse the two multilayers in opposite directions ͑i.e., Tb to Fe and Fe to Tb͒. 29 Sensitivity to Fe-on-Tb interface was achieved by depositing a 0.5 nm thick 57 Fe marker layer at the interface, and using conversion electron Mössbauer spectroscopy to detect the changes at the interface. It was concluded that intermixing at the Fe/ Tb interface is not affected by the direction in which 11.…”
Section: Resultsmentioning
confidence: 99%
“…No change in the average composition of the mixed Tb/Fe interface was observed when the incident ion direction is changed from a Tb layer to a Fe layer or vice versa. The authors suggested that the basic mechanism which allows converting the energy transferred to the electronic subsystem into atomic motion leading to interfacial mixing is independent of the relative position of the different layers with respect to the incident beam direction [559].…”
Section: Metal/metalmentioning
confidence: 99%
“…Inside this tracks, amorphization of crystalline material may be induced. Several transformations in magnetic materials have been reported such as increase of coercivity by domain wall pinning in permanent magnet [3] or atomic mixing at the interfaces in magnetic Fe/Tb multilayers [4].…”
Section: Introductionmentioning
confidence: 99%